Maya Christina Gonzalez Interview - Arne Nixon Center for the Study of Children's Literature; Gonzalez, Maya Christina
Maya Christina Gonzalez has been awarded the Arne Nixon Center Artist-in-Residence Fellowship for fall of 2017.